The mediating effect of employee commitment towards organization effectiveness framework - Isa, Khairunesa; Md. Yusoff, Rosman; Rahman Ahmad, Abd.; Hanim Nadrah Wan, Wan (International Journal of Engineering and Technology, 2018)
The main purpose of this paper is to study the mediating effect of employeeâ€™s commitment between leadership style and organization effectiveness. In addition, it presents a conceptual research framework to understand these relationships as supported by literature review from recent studies. The main findings indicate that employee commitment can be partial mediator factor between leadership style and organization effectiveness. To get the commitment, leaders should empower employees through human orientation and the application of transformational leadership elements such as intellectual stimulation and individual consideration which help to create mutual understanding between employees and organization. In conclusion, employee commitment plays a role as partial mediator between leadership style and organization effectiveness.Â